ANALISIS PENGARUH KINERJA KEUANGAN DAN ISLAMIC CORPORATE SOCIAL RESPONSIBILITY (ICSR) TERHADAP PENGELUARAN ZAKAT PERUSAHAAN (Studi Kasus Bank Umum Syariah di Indonesia Tahun 2017-2021): (Studi Kasus Bank Umum Syariah di Indonesia Tahun 2017-2021) - Tathia Rizki Alika; Fatimah Annisa; Diana Nurindrasari (Prodi Akuntansi FE Universitas Maritim Raja Ali Haji, 2023)
This study aims to analyze the effect of the financial performance and Islamic Corporate Social Responsibility (ICSR) on the corporate zakat in sharia commercial banks in 2017-2021. This study uses a quantitative approach with the population of 15 Islamic Commercial Banks in Indonesia registered with the OJK in 2017-2021. The source of data comes from secondary data in the form of financial statements and annual reports contained in each company's website. The samples are 6 Islamic Commercial Banks obtained by using a purposive sampling method. Data analysis used is a multiple linear regression test. The results of this study indicate that partially ROA has no a significant effect on the company's zakat, ROE has a significant effect on the company's zakat, NOM has no a significant effect on the company’s zakat, and Islamic Corporate Social Responsibility (ICSR) has a significant effect on the company's zakat. Meanwhile, simultaneously, the financial performance and Islamic Corporate Social Responsibility (ICSR) have an effect on the company's zakat.